Probability theory and statistical inference : econometric modeling with observational data - Spanos, Aris, 1952- (Cambridge University Press, 1999)
The primary objective of this text is to establish the framework for the empirical modelling of observational (non-experimental) data. The book is aimed at students taking introductory courses in proabilitity theory and statistical inference.